Judicial Adaptability: Research on Judicial Activism and the Principle of Separation of Powers in Common Law - Wang, Yijun (International Journal of Social Sciences and Public Administration, 2024)
The relationship between judicial activism and separation of powers has been a hot topic in the judicial field. This paper studies the consistency between judicial activism and the principle of separation of powers in common law. Judicial activism involves judges taking an active role in promoting legal and social change, thereby challenging the traditional judicial role. The main argument is that judicial activism is essential to maintain the adaptability and flexibility of the law, especially in a rapidly changing social, technological and economic environment. Through the analysis of landmark cases such as Mabo v Queensland, No. 2 and R v Dugan, this paper shows how judicial activism can address legislative gaps to ensure justice and equity. In addition, it discusses the need to improve the legal framework to enable judges to make proactive decisions within clearly defined parameters. The conclusions highlight the indispensable role of judicial activism in maintaining a dynamic and responsive legal system, upholding democratic values, and preserving public trust.